Evaluation and Formulation of Lip Balm Preparation From Aloe Vera (Aloe Vera) and Bit (Beta Vulgaris) Fruit Extract as Natural Dye - Hafni Nur Insan; Yulia Vera (Journal of Public Health and Pharmacy, 2021)
Lip balm is a cosmetic preparation that is useful for moisturizing and shiny lips. The purpose of this study was to formulate lip balm preparations using Bit Fruit Extract (Beta Vulgaris) and to evaluate its effectiveness as a lip moisturizer. Beetroot extract (Beta Vulgaris) was formulated with concentrations of 0%, 6%, 8%, and 10%, as a blank used lip balm base. Tests on lip balm preparations include homogeneity test, pH measurement, irritation test and stability test of the preparation with parameters such as odor, color and pH during 12 weeks of storage. Bit (Beta Vulgaris) extract lip balm with a concentration of 10% can provide a moisturizing effect Lips are best at restoring lip skin after 4 weeks.